Thermal conductivity measurement of nanostructures - Lim, Yuwei. (2009)
This experiment presents to you the extraction of thermal properties of single wall carbon nanotube bundles from our 3 layered samples using the Pulsed Photothermal Reflectance technique. The top layer of the sample is a gold film, the second layer is silicon dioxide or CNT array and the bottom layer being the silicon substrate. Two silicon dioxide samples of different thickness will be used to verify the accuracy of our setup and three CNT samples of different thickness will be measured and investigated. For modeling, we utilized the transmission-line theory for curve fitting. The mean value of the thermal conductivity of our CNT samples were 0.65 W/mK for 2 um CNT thickness, 1.06 W/mK for 4 um and 1.12 W/mK for 5 um.